(untitled) (Asian Journal of Medical and Biological Research, 2016)
The aim of this research was to observe the effect of heat stress on milk yield and milk compositions of Holstein Friesian crossbred (HF) dairy cows. To fulfill the objectives, a total of 9 Holstein Friesian crossbred cows were selected for this study. Green grasses (German, Para) were supplied adlibitum and concentrate feeds (mixture of wheat bran, rice polish, mustard oil cake, di-calcium phosphate and salt) were supplied at the rate of 2.0 kg/day/cow. Management practices for all the cows were similar following the BAU Dairy farm practices. Data were collected on milk yield (l/h/d), relative humidity (%) and barn temperature (0C). The obtained temperature humidity index (THI) of July, August, September and October were 84.95, 81.99, 81.40 and 79.57, respectively. The highest THI was found in July which indicated higher heat stress during this month. A significant difference (p<0.05) in milk yield of cows was found among different months of July to October. The highest milk yield (6.10±0.50 l/h/d) was found in October among observed months. The compositions of milk such as total solids (TS), solids-not-fat (SNF), fat, protein, lactose, and ash also differed significantly (p<0.01). The highest values (%) of TS, SNF, fat, protein, lactose and ash content of milk were found in October as 12.63, 8.80, 3.83, 3.69, 4.39 and 0.72, respectively and lowest values (%) were in July as 12.20, 8.50, 3.71, 3.50, 4.30 and 0.69, respectively due to the high THI value. From these results, it is concluded that heat stress has strong effect on milk yield and milk composition of HF cows in Bangladesh. Management strategies are needed to minimize heat stress and attain optimal dairy animal performance. Asian J. Med. Biol. Res. June 2016, 2(2): 190-195